E-counselling with persuasive design: a prototype / Hazwani Mohd Mohadis - Mohd Mohadis, Hazwani (2010)
E-counselling is an exciting new method of helping people work through life issues. As counselling process mainly aims at changing people's behaviour and thinking, it is vitally important for an e-Counselling website to be highly persuasive. For the purposes of this project, persuasiveness of "e-Kaunseling Pelajar" has been investigated by conducting usability testing. Analysis of usability testing conducted on this website proves that this website is lack of persuasiveness elements which in turn results in less participation. Accordingly, this project aims to develop a prototype of e- Counselling website which utilizes persuasive design techniques.